SELF DISCLOSURE DALAM MEMBENTUK LEVEL HUBUNGAN INTERPERSONAL PERSPEKTIF GENDER DI ASRAMA PUTRA DAN PUTRI STAIN PAREPARE - Hasniar Hasniar; Muhammad Qadaruddin; Nurhakki Nurhakki (KOMUNIDA : Media Komunikasi dan Dakwah, 2018)
Self-disclosure or "self disclosure" can be interpreted as giving information about yourself to others. The information provided can include various things such as life experiences, feelings, emotions, opinions, ideals, etc. Self-disclosure needs to be done by the dormitory because it is one way to adapt to the new environment. Self-disclosure, among others, is influenced by gender differences. Self-disclosure is closely related to effective interpersonal communication. The type of research conducted by the researcher is descriptive qualitative research using interviews, observation and documentation to find the data to be analyzed using triangulation techniques. The results of this study indicate that STAIN Parepare male dormitory and female dormitory students are able to build interpersonal relationships by means of self-disclosure and are able to provide an overview of the existence of gender differences in terms of the process of building interpersonal relationships. The relationship stage that can be formed through the sixth stage of the process becomes a reference for discussion to develop interpersonal relationships. Interpersonal relationships that occur in the STAIN Parepare male and female dormitories are in the management of psychological data levels to be able to do self disclosure. son or being in the category area area, the purpose of open area is where the residents of STAIN Parepare dormitories are more at an open level in order to be able to build good relationships. Self disclosure is a good system that is also applied by residents of the Parepare STAIN dormitory to form interpersonal relationships.